ECOLOGICAL CRISIS AS A CULTURAL PHENOMENON - Shermatova Zamira Sherzod kizi (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
Theoretical biology actively addresses the doctrine of man as a whole. The reasons for this are simple and fundamental. Knowledge is human knowledge, and man is a living being. Biology is a special part of culture and works within the framework of thinking aimed at comprehending reality. It is important that for this direction of theoretical biology the basis is life as a biological and cultural phenomenon in the broad sense.